2018
DOI: 10.3177/jnsv.64.432
|View full text |Cite
|
Sign up to set email alerts
|

Association of Circulating 25-Hydroxyvitamin D Levels with Colorectal Cancer: An Updated Meta-Analysis

Abstract: A higher serum 25-hydroxyvitamin D (25(OH)D) concentration benefits colorectal cancer prevention. However, whether it can improve the prognosis among patients is still under discussion. This study aims to explore the impacts of high level 25(OH)D on the survival of colorectal cancer patients. PubMed, Embase, and Cochrane were searched from January 2000 to August 2017 for relevant articles. Only published studies focusing on the relationship between 25(OH)D levels at or near the time of diagnosis and survival w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 52 publications
(206 reference statements)
2
14
0
Order By: Relevance
“…As for staging, TNM staging remained a strong tool for establishing prognosis and directing therapy [ 62 ]. No significant heterogeneity among the studies was found for CRC-specific survival in our study ( I 2 = 0%), which was similar to the results of Maalmi et al However, the meta-analysis conducted by Xu et al, showed a significant heterogeneity ( I 2 = 69%), which might because of less studies they included [ 30 ].…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…As for staging, TNM staging remained a strong tool for establishing prognosis and directing therapy [ 62 ]. No significant heterogeneity among the studies was found for CRC-specific survival in our study ( I 2 = 0%), which was similar to the results of Maalmi et al However, the meta-analysis conducted by Xu et al, showed a significant heterogeneity ( I 2 = 69%), which might because of less studies they included [ 30 ].…”
Section: Discussionsupporting
confidence: 89%
“…The HR (95% CI) for overall and CRC-specific survival in CRC patients from our study was similar to the previous meta-analyses [ 29 , 30 ]. However, our study showed a lower heterogeneity for overall survival than those in the two meta-analyses.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations